A GO/CoMo3S13 chalcogel heterostructure with rich catalytic Mo-S-Co bridge sites for the hydrogen evolution reaction - Ha Thanh Duy Cam; Do Ha Huu; LEE, HEE HYEON; Ha Nguyen Ngoc; Ha Nguyen Thi Thu; Ahn Sang Hyun; Oh Youngtak; Kim Soo Young; Kim Myung-Gil (Royal Society of Chemistry, 2022)
Molybdenum disulfide (MoS2)-based materials are extensively studied as promising hydrogen evolution reaction (HER) catalysts. In order to bring out the full potential of chalcogenide chemistry, precise control over the active sulfur sites and enhancement of electronic conductivity need to be achieved. This study develops a highly active HER catalyst with an optimized active site-controlled cobalt molybdenum sulfide (CoMo3S13) chalcogel/graphene oxide aerogel heterostructure. The highly active CoMo3S13 chalcogel catalyst was achieved by the synergetic catalytic sites of [Mo3S13](2-) and the Mo-S-Co bridge. The optimized GO/CoMo3S13 chalcogel heterostructure catalyst exhibited high catalytic HER performance with an overvoltage of 130 mV, a current density of 10 mA cm(-2), a small Tafel slope of 40.1 mV dec(-1), and remarkable stability after 12 h of testing. This study presents a successful example of a synergistic heterostructure exploiting both the appealing electrical functionality of GO and catalytically active [Mo3S13](2-) sites.